INTEGRATED MANAGEMENT OF SIGATOKA LEAFSPOT OF BANANA - GURUDATT M. HEGDE; RAGHAVENDRA K. MESTA (The Bioscan, 2014)
A field experiment was conducted to manage banana sigatoka leafspot disease at Uttara Kannada district of Karnataka for consecutive two seasons (2008-09 and 2009-10). The plots sprayed thrice with Hexaconazole @0.1% has significantly reduced the disease incidence to the extent of 13.74% which is on par with three sprays of propiconazole (16.07%) and spray with Psuedomonas fluorescens (P)+ Bacillus subtilis (Bs)-P+Bs-P+Bs @ 0.1% and 0.5% (15.21%) respectively. The effectiveness of the fungicides was judged on the basis of increased yield per unit along with reduced disease intensity. Experimental results proved the effectiveness of P+Bs-P+BsP+Bs @ 0.1% and 0.5% treatment by recording significantly highest banana yield (42.13t/ha) and reduced disease pressure (15.21%) and which was at par with consecutive three sprays of hexaconazole (42.0t/ha) and propiconazole (41.49t/ha). The cost economics indicated highest net return in hexaconazole (Rs.56350.00) treatment and which was followed by P+Bs-P+Bs-P+Bs (Rs.54,220.00)and propiconazole (Rs. 52,660.00) treatments. Thus, a new triazole molecule hexaconazole could be used as an alternate molecule to manage sigatoka leaf spot disease in banana.